Implementation of construction informatics to improve the pre and postproduction of precast supply chain - Sim, Aaron Jie Hao (Nanyang Technological University, 2020)
Precast concretes are cast and cured offsite in a controlled environment before they are brought to site to be installed. This process allows them to have advantages over cast-in-situ concretes, such as better quality, shorter construction time, etc. One of main factors that would affect the efficiency of the precast process greatly is its supply chain. In this paper, value stream mapping, a production method, will be used on a precast manufacturer’s supply chain to identify the possible areas of improvements (current state map) Improvements were made through the application of RFID technology, BIM and network platforms to achieve an enhanced supply chain (future state map). The two stream maps are compared to analyze how the changes in system effect the productivity and efficiency of the supply chain.